2021
DOI: 10.1111/cge.14100
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing genetic counseling and testing for hereditary breast and ovarian cancer syndrome in a large US health care system

Abstract: Investigate whether disparities and other factors influence referral to genetic counseling and testing for hereditary breast and ovarian cancer syndrome (HBOC) in a large health care system. Examination of clinical, demographic, and socioeconomic factors from electronic health records associated with genetic referral and testing within 12 months after a new cancer diagnosed between August 1, 2013 and December 31, 2018. For patients meeting institutional criteria for HBOC testing, 60.6% were referred for geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…Respondents from the province of British Columbia or who were >50 years old at diagnosis were also more likely, and those from the province of Saskatchewan were less likely, to be offered genetic testing. The greater proportion of respondents >50 years being offered genetic testing (78% vs. 66% for <50) is contrary to previous studies reporting an increased uptake of genetic testing in younger cancer patients [32,33]; however, ours was not an unselected sampling of OC patients and therefore cannot be directly compared to these reports.…”
Section: Discussioncontrasting
confidence: 77%
“…Respondents from the province of British Columbia or who were >50 years old at diagnosis were also more likely, and those from the province of Saskatchewan were less likely, to be offered genetic testing. The greater proportion of respondents >50 years being offered genetic testing (78% vs. 66% for <50) is contrary to previous studies reporting an increased uptake of genetic testing in younger cancer patients [32,33]; however, ours was not an unselected sampling of OC patients and therefore cannot be directly compared to these reports.…”
Section: Discussioncontrasting
confidence: 77%
“…2 When examining disparities based on race or ethnicity, Lau-Min et al found that Black race was associated with a lower rate of genetic testing compared with White race, a gap that has been previously reported. 2,4,6 In other studies, Asian ancestry has also found to be associated with lower rates of genetic testing, 4,5 and Latinas were more likely to report that they received too much information about testing. 3 For patients who undergo genetic testing, individuals of non-European ancestry have higher rates of variants of uncertain significance (VUS).…”
mentioning
confidence: 81%
“…Non-Hispanic white (NHW) patients are more likely to be recommended for genetic counseling, referred, and undergo genetic testing. 23 24 25 Despite the higher rates of CRC and increased prevalence of Lynch syndrome in African Americans, referral rates (even for those with abnormal immunohistochemistry [IHC]) and genetic testing are significantly lower compared with NHW. 26 Systemic biases may be present in existing guidelines which were developed from NHW populations.…”
Section: Population Testing Outside the Setting Of A Specific Phenoty...mentioning
confidence: 99%